Multi-target-directed therapeutic potential of 7-methoxytacrine-adamantylamine heterodimers in the Alzheimer's disease treatment - Gazova, Zuzana; Soukup, Ondrej; Sepsova, Vendula; Siposova, Katarina; Drtinova, Lucie; Jost, Petr; Spilovska, Katarina; Korabecny, Jan; Nepovimova, Eugenie; Fedunova, Diana; Horak, Martin; Kaniakova, Martina; et al. (Biochimica et biophysica acta. Molecular basis of disease, 2017)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder and currently there is no efficient treatment. The classic drug-design strategy based on the "one-molecule-one-target" paradigm was found to be ineffective in the case of multifactorial diseases like AD. A novel multi-target-directed ligand strategy based on the assumption that a single compound consisting of two or more distinct pharmacophores is able to hit multiple targets has been proposed as promising. Herein, we investigated 7-methoxytacrine - memantine heterodimers developed with respect to the multi-target-directed ligand theory. The spectroscopic, microscopic and cell culture methods were used for systematic investigation of the interference of the heterodimers with β-secretase (BACE1) activity, Aβ peptide amyloid fibrillization (amyloid theory) and interaction with M1 subtype of muscarinic (mAChRs), nicotinic (nAChRs) acetylcholine receptors (cholinergic theory) and N-methyl-d-aspartate receptors (NMDA) (glutamatergic theory). The drug-like properties of selected compounds have been evaluated from the point of view of blood-brain barrier penetration and cell proliferation. We have confirmed the multipotent effect of novel series of compounds. They inhibited effectively Aβ peptide amyloid fibrillization and affected the BACE1 activity. Moreover, they have AChE inhibitory potency but they could not potentiate cholinergic transmission via direct interaction with cholinergic receptors. All compounds were reported to act as an antagonist of both M1 muscarinic and muscle-type nicotinic receptors. We have found that 7-methoxytacrine - memantine heterodimers are able to hit multiple targets associated with Alzheimer's disease and thus, have a potential clinical impact for slowing or blocking the neurodegenerative process related to this disease.
Keywords: sekretasy; Aggregation; CHO buňky; takrin; Humans; amantadin; cholinesterasy; dimerizace; Molecular Targeted Therapy; Amyloid Precursor Protein Secretases; Receptors, N-Methyl-D-Aspartate; Dimerization; Aβ peptide; lidé; Alzheimer Disease; Xenopus; zvířata; Alzheimerova nemoc; amyloidní beta-protein; HEK293 Cells; CHO Cells; Cricetulus; receptory cholinergní; receptory N-methyl-D-aspartátu; Amyloid; Amyloid beta-Peptides; Cholinesterases; Muscarinic/nicotinic acetylcholine receptor antagonist; Receptors, Cholinergic; HEK293 buňky; cílená molekulární terapie; Alzheimer's disease; inhibitory enzymů; Receptor, Muscarinic M1; Tacrine; Animals; receptor muskarinový M1; β-Secretase inhibitor; Enzyme Inhibitors; Amantadine; N-Methyl-d-aspartate receptor antagonist